ANALYSIS OF PROBLEM SOLVING CYCLE (PSC) IN ACCOUNTING AND FINANCIAL REPORTING IN REGIONAL GENERAL SERVICES AGENCY - Widyajasita, Aulia (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
Public Service Agency Hospital is a general government agency whose activities are also selling goods or services. Financial statements are a tool for making rational decisions in sound business practices. The financial reporting process for Hospital BLU has been regulated in the Minister of Finance Regulation Number 76/PMK.05/2008 concerning Guidelines for Accounting and Financial Reporting for Public Service Agencies and the Decree of the Minister of Health of the Republic of Indonesia Number 1981/MENKES/SK/XII/2010 concerning Accounting Guidelines for Service Agencies. General (BLU) Hospital. The method used is a literature study of journals on Financial Statements in several BLUDs, as many as 10 journals, and the stages of Situation Analysis, Problem Identification, Problem Priority Determination, Problem Alternative Development, and Plan of Action are carried out. The results of the PSC analysis obtained that the priority problems were "The reporting system is not by KMK No. 1981 the Year 2010 and PMK No. 76 of 2008", so problem development and alternative search for problems were carried out starting with fishbone analysis and caused five main issues; namely, Lack of financial reporting staff who understand the contents of KMK No. 1981 the Year 2010, a recording system that is not yet computerized, does not use an accrual basis of reporting system, the reporting system is not made monthly but is carried out only at the end of the year, Expenditures are greater than Revenues, thus confusing reports every year. So it is recommended in the Plan of Action several activities to solve the problem.